1991
DOI: 10.1128/jvi.65.12.6553-6561.1991
|View full text |Cite
|
Sign up to set email alerts
|

Simian virus 40 small-t does not transactivate RNA polymerase II promoters in virus infections

Abstract: Transcriptional stimulatory properties of virus-encoded transactivators appear to be critical for viral gene expression and may be linked to cellular transformation in certain cases. Recently, the simian virus 40 (SV40) 17-kDa small-t antigen was shown to stimulate transcription of polymerase II and III genes in transient transfection assays. In experiments performed in our laboratory, two of the polymerase II promoters of the adenovirus genome, namely, the ElI-early and EIII promoters, were transactivated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1992
1992
1999
1999

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Effect of the 97-103 region mutations on transactivation. Another known function of small-t antigen is its ability to transactivate the adenovirus E2 promoter (12,13,19). To determine whether the Cys 97-103 region played a role in this activity, the mutations were cloned into plasmid pw2t for cotransfection with a plasmid in which chloramphenicol acetyltransferase was expressed under the control of the adenovirus E2 promoter as in earlier studies (9, 19).…”
Section: Small-t Transformation and Pp2a Inhibitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Effect of the 97-103 region mutations on transactivation. Another known function of small-t antigen is its ability to transactivate the adenovirus E2 promoter (12,13,19). To determine whether the Cys 97-103 region played a role in this activity, the mutations were cloned into plasmid pw2t for cotransfection with a plasmid in which chloramphenicol acetyltransferase was expressed under the control of the adenovirus E2 promoter as in earlier studies (9, 19).…”
Section: Small-t Transformation and Pp2a Inhibitionmentioning
confidence: 99%
“…It has also been shown that small-t can transactivate polymerase II-and polymerase 111-directed transcription from a variety of promoters when cotransfected with reporter constructs (13). The relevance of this observation to infection has been called into question by the failure of small-t expressed from an adenovirus vector to activate transcription of the adenovirus E2 promoter (19). Small-t transactivation appears to require E2F-binding sites in the E2 promoter (12).…”
mentioning
confidence: 99%
“…The unique carboxyl termini of the small t antigens are created by differential splicing of a common precursor mRNA. The SV40 small t antigen has been reported to transactivate the adenovirus E2 promoter in some contexts (17) but not in others (29). In addition, the small t antigens from PyV and SV40 have been shown to form a complex with the catalytic subunit and one regulatory subunit of protein phosphatase 2A (21,43).…”
Section: Small T Antigens All Polyomaviruses Contain An Open Reading mentioning
confidence: 99%